The Establishment of Youth Posyandu to Increase Adolescent's Productivity - Dwie Yunita Baska; Wewet Savitri; Nispi Yulyana (DIKDIMAS : Jurnal Pengabdian Kepada Masyarakat, 2023)
The complexity of health problems in adolescents needed requires an comprehensive and integrated treatment that involves all elements across the programs and related sectors. Youth Posyandu was a solution that can be offered to community. This activities aims as a forum that brings together adolescent or youth in managing and facilitating them to getting informations which is about healthy lifestyle, adolescent reproductive health and other health problems. The methods used include 3 steps: preparation, actions, and evaluation. The location was in Lempuing, Ratu Agung District, Bengkulu City, and involving 25 adolescents. The results of the activity showed that the establishment of the youth Posyandu in Lempuing had a positive impact on partners. In conclusion, this youth Posyandu makes it easier for teenagers to obtain information related to a healthy lifestyle, forms youth support groups, and becomes a forum that facilitates youth in understanding their daily problems.